Gingival primary extranodal non-Hodgkin's lymphoma as the first manifestation of acquired immunodeficiency syndrome - Navarro, Cláudia Maria [UNESP]; Shibli, Jamil A.; Ferrari, Roberto B.; d'Avila, Susana; Sposto, Maria R. [UNESP] (Amer Acad Periodontology, 2008)
Background: Non-Hodgkin's lymphomas (NHLs) are a heterogeneous group of lymphoproliferative malignancies that may be associated with acquired immunodeficiency syndrome (AIDS). NHL can disseminate to extranodal sites; however, its dissemination to the jaws and mouth is not common. This report presents and discusses two unusual cases of gingival primary extranodal non-Hodgkin's lymphoma (PE-NHL) as the first manifestation of AIDS.Methods: Two mates presented with asymptomatic gingival swelling. They were examined clinically. Biopsies of the gingival tissue were evaluated using routine histologic techniques and immunohistochemistry. The patients were tested for human immunodeficiency virus (HIV) infection.Results: The clinicopathological evaluation and the serological HIV examination of the patients led us to the final diagnosis of gingival PE-NHL as the first manifestation of AIDS. Both patients were referred to an oncologist and to an infectious disease specialist and were given antineoplastic chemotherapy and highly active antiretroviral therapy. Only one patient presented a favorable clinical evolution.Conclusion: The present case reports have important clinical implications; the two unusual presentations of gingival PE-NHL contribute to information about the differential diagnosis of rapidly progressing gingival swelling.
Keywords: AIDS; case report; gingiva; HIV; non-Hodgkin's; lymphoma